Toward increasing Security and Role of Encryption Key for Computer based Encryption System (Al-Mansour Journal, 2022)
Cryptography is the science of using mathematics to encrypt and decrypt data. Cryptography enables us to store or transmit sensitive information across insecure channel (like Internet), by making it unreadable except to intended recipient .A key is a value that works with a cryptographic algorithm to produce a specific cipher text .The bigger the key, the more security that we will gain. In the case when encryption system was executed on personal computer connected to the net or on the net server itself, the encrypted data security depends on: • The strength of the cryptographic algorithm.• The secrecy of key storage method and its immunity against direct physical attacks, or attacks from net.There are many traditional ways for storing encryption keys (floppy disk, PC hard drive ,paper in our pocket ,paper stored in locked cabinet … ,etc ) .In this research there will be a try to increase the encrypted data security through two directions ,first by increasing the security of key storage by introducing a untraditional hardware physical module for that purpose ,and the second by increasing the role of encryption key into encryption algorithm executed on computer through :• Introduce a new way for entity (user) authentication.• Design of external hardware module attached to PC parallel port to improve encryption key storage security and Role.• Gaining improvement in the security level for PC based encryption system (or any other microprocessor based) encryption system.